Atherogenic Risk Factors in Medical Students - Airam Navarro Palacios; Miguel Ángel Serra Valdés; Rafael Comas Valdespino; Girelda Cordero López; Alain Landrian Davis; Adrian Landrian Davis (Universidad de las Ciencias Médicas de Cienfuegos, 2020)
Background: atherosclerosis is a multifactorial origin disease. The study and approach of its modifiable risk factors and action on these factors can positively change the health situation. Objective: to identify some early atherogenic signs in second-year medical students at the Dr. Enrique Cabrera Medical Sciences Faculty in Havana. Method: a descriptive study was carried out to identify some atherogenic risk factors between 2018 and 2019, which included 170 students of cuban nationality who were studying the second year of medicine at the Dr. Enrique Cabrera Faculty of Medical Sciences, with ages between 19 and 24 years old, of both sexes and did not report any symptoms or disease. Survey was applied, made for this purpose and validated by the Atherosclerosis Center for Research and References of Havana modified. The variables considered were: sex, body mass index (BMI), smoking habit, arterial hypertension, hypercholesterolemia, hypertriglyceridemia, nutritional habits, alcohol consumption and family pathological history. Results: the most frequent atherogenic risk factors detected were: obesity (17.65 %), dyslipidemia (16.7 %), smoking (33.5 %), arterial hypertension (9.4 %), frequent consumption of alcoholic beverages (28.2 %), related family pathological history (22.9 %) and inadequate diets (62.2 %), whose values in the statistical analysis were significant. More than the 40 % of the patients had two or more risk factors. Conclusions: the results showed high numbers of risk factors, alone or in combination. The risk factors that predominated were smoking, poor nutritional habits, dyslipidemia and the ingestion of alcoholic beverages.